(untitled) (World Bulletin of Social Sciences, 2025)
This article explores the intricate relationship between culture, reading, and the development of spiritual and moral values in young people. The author contends that, within the context of a technogenic civilization – characterized by the erosion of spiritual and moral frameworks – there exists a significant risk of the devaluation of cultural and moral values. The paper underscores the importance of reading culture as an integral component of the broader cultural system, suggesting that it has the potential to serve as a safeguard against the spiritual depersonalization of youth. In addressing this challenge, the author proposes that social and institutional structures, such as preschools, schools, mahallas, and khokimiyats, should take an active role in fostering the development of spiritual values.